Lymphocyte Counts and Multiple Sclerosis Therapeutics: Between Mechanisms of Action and Treatment-Limiting Side Effects - Stefanie Fischer; Undine Proschmann; Katja Akgün; Tjalf Ziemssen (Cells, 2021)
Although the detailed pathogenesis of multiple sclerosis (MS) is not completely understood, a broad range of disease-modifying therapies (DMTs) are available. A common side effect of nearly every MS therapeutic agent is lymphopenia, which can be both beneficial and, in some cases, treatment-limiting. A sound knowledge of the underlying mechanism of action of the selected agent is required in order to understand treatment-associated changes in white blood cell counts, as well as monitoring consequences. This review is a comprehensive summary of the currently available DMTs with regard to their effects on lymphocyte count. In the first part, we describe important general information about the role of lymphocytes in the course of MS and the essentials of lymphopenic states. In the second part, we introduce the different DMTs according to their underlying mechanism of action, summarizing recommendations for lymphocyte monitoring and definitions of lymphocyte thresholds for different therapeutic regimens.